2020
DOI: 10.3389/fimmu.2020.566893
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan-Induced Trained Immunity in Dogs

Abstract: Several observations in the world of comparative immunology in plants, insects, fish and eventually mammals lead to the discovery of trained immunity in the early 2010's. The first demonstrations provided evidence that innate immune cells were capable of developing memory after a first encounter with some pathogens. Trained immunity in mammals was initially described in monocytes with the Bacille Calmette-Guerin vaccine (BCG) or prototypical agonists like β-glucans. This phenomenon relies on epigenetic and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Trained immunity is a non-specific immune response arising from vaccination or infection that enhances the responsiveness of immune cells such as monocytes, macrophages, and natural killer (NK) cells to further heterologous infections [ 9 , 10 ]. This phenomenon occurs in the hematopoietic stem cells of the bone marrow, and the effects can be seen in the myeloid progenitors [ 9 , 11 , 12 ]. The trained phenotype observed in immune and endothelial cells has been attributed to epigenetic modifications [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trained immunity is a non-specific immune response arising from vaccination or infection that enhances the responsiveness of immune cells such as monocytes, macrophages, and natural killer (NK) cells to further heterologous infections [ 9 , 10 ]. This phenomenon occurs in the hematopoietic stem cells of the bone marrow, and the effects can be seen in the myeloid progenitors [ 9 , 11 , 12 ]. The trained phenotype observed in immune and endothelial cells has been attributed to epigenetic modifications [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trained immunity is an evolutionarily conservative innate immune mechanism that exists in multiple vertebrate species including mammals [ 26 ], chickens [ 28 ], and fishes [ 42 ]. This study showed that exposure to C. perfringens increases the production of NO in primed PBMC compared to non-primed.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of b-glucans by Dectin-1 has been shown to induce epigenetic modifications in immune cells, that render them more efficient in responding to infection (66), a phenomenon referred to as trained immunity (66,67). It is therefore conceivable that bovine monocytes, such as those of mice (68), humans (28), dogs (69), and chicken (70) may be prone to induction of trained immunity. That would provide a plausible explanation for the beneficial effects of b-glucancontaining dietary supplements observed in vivo in cattle (23,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%